ROTEAMENTO AUTOMÁTICO DE ALIMENTADORES NO PLANEJAMENTO DE SISTEMAS DE DISTRIBUIÇÃO DE ENERGIA ELÉTRICA - ROCHA, Adson Silva (2008)
The present work deals with the problem of planning the distribution system of electricity and is divided into three parts: Problem Definition, Resolution Approaches and Results and Conclusions. The energy distribution networks are of great economic importance in countries like Brazil. On one hand, there are fixed costs of physical installation and operation of the network, mainly due to the costs of energy losses and, secondly, the natural obstacles along the possible passages of network s links. The large amount of these costs, together with lack of efficient methods when it comes to real applications in the matter, justify the development of this research. The study of such aspects, the precise definition of the problem and the reasons that motivated this work can be found on the first part of this work. The second part shows the approaches for resolution. Three proposals methods were adopted: the first uses the algorithm Prim associated with the method Nelder-Mead Simplex. In the second proposal uses Dynamic Programming and, finally, we take the metaphor of Ant Colony also associated with the Nelder-Mead Simplex. The results, presented at the third part of this work, demonstrated the effectiveness of the proposed methods, especially the good compromise between performance and applicability obtained by the third proposal.